Vespers rising - Riordan, Rick; Lerangis, Peter; Korman, Gordon; Watson, Jude (New York : Scholastic, 2011)
Fourteen-year-old Amy Cahill and her younger brother Dan thought they could return to their regular lives when they found the 39 clues. But the Vespers, powerful enemies, will stop at nothing to get the clues. And with the Vespers rising, the world is in jeopardy.
Gideon Cahill : 1507 / Rick Riordan -- Madeleine Cahill : 1526 / Peter Lerangis -- Grace Cahill : 1942 / Gordon Korman -- Amy and Dan Cahill present / Jude Watson.
Accelerated Reader AR
Reading Counts RC
106377
Keywords: Brothers and sisters -- Juvenile fiction; Orphans -- Juvenile fiction; Family secrets -- Juvenile fiction; Adventure and adventurers -- Fiction; Siblings -- Fiction; Secrecy -- Fiction; Adventure stories; Children's stories; Action and adventure fiction; Fiction; Juvenile works; Mystery fiction; Action and adventure fiction